Long-term Comparative Outcomes of Carotid Artery Stenting Following Previous Carotid Endarterectomy vs De Novo Lesions. (June 2015) - Mousa, Albeir Y.; AbuRahma, Ali F.; Bozzay, Joseph; Broce, Mike; Kali, Maher; Yacoub, Michael; Stone, Patrick; Bates, Mark C.
Purpose: To report the long-term outcomes of patients who underwent carotid artery stenting (CAS) for de novo carotid stenosis vs patients treated for restenosis after carotid endarterectomy (CEA).Methods: A retrospective review was conducted of all 385 patients (mean age 68.6±9.6 years; 231 men) who underwent 435 CAS procedures at a large tertiary care center between January 1999 and December 2013. For analysis, patients were stratified based on their lesion type [de novo (dn) vs post-CEA restenosis (res)] and subclassified by symptoms status [symptomatic (Sx) or asymptomatic (Asx)], creating 4 groups: (1) CAS-dn Asx, (2) CAS-dn Sx, (3) CAS-res Asx, and (4) CAS-res Sx. For the CAS-res group, the mean elapsed time from CEA to CAS was 72.4±63.6 months. Outcomes included target vessel reintervention (TVR) and in-stent restenosis (ISR), the latter defined by a carotid duplex ultrasound velocity >275 cm/s.Results: The main indication for initial carotid angiography with possible revascularization was severe carotid stenosis (≥70%-99% on duplex) in both CAS-dn and CAS-res groups (83.6% vs 83.7%, p=0.999). There were no significant differences in the percentage of patients with postintervention residual stenosis (<30%; 100% each arm) or complications between CAS-res vs CAS-dn: in-hospital stroke (1.4% vs 1.8%, respectively), myocardial infarction (0.9% vs 0%), or death (0.9% vs 0%). Mean follow-up was 62.4±45.6 months (median 53.5, range 1–180). Average clinical/TVR follow-up was greater for the CAS-res group (71.9±48.6 months) compared with 53.3±40.5 months for the CAS-dn group (p<0.001). Across the 4 study groups, there were no differences in freedom from ISR (p=0.174) or TVR (p=0.856). Multivariate analysis found peripheral vascular disease (PVD) as the sole ISR independent predictor [hazard ratio (HR) 1.92, 95% confidence interval (CI) 1.03 to 3.62, p=0.041], while significant predictors for TVR were age <65 years at the time of the procedure (HR 2.55, 95% CI 1.05 to 6.18, p=0.039) and PVD (HR 2.46, 95% CI 1.03 to 5.87, p=0.043).Conclusion: The current study suggests that CAS is a feasible and durable therapeutic option for recurrent restenosis after CEA. Long-term outcomes were similar for patients treated for de novo lesions or post-CEA restenosis. Age and PVD appear to influence long-term CAS durability.